2022
DOI: 10.1021/acsomega.1c05378
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Approaches toward the Synthesis of Brivaracetam: An Antiepileptic Drug

Abstract: Epilepsy is a chronic neurological disorder in the brain, affecting individuals of all age groups. Nearly 1% of the world population is affected by seizure disorder, of which 80% of the patients are observed in underdeveloped and developing countries. The predominant treatment option for epilepsy includes an antiepileptic drug named brivaracetam. This drug emerged as an unusual success of rational drug discovery in clinical development by exhibiting magnificent affinity toward synaptic vesicle glycoprotein as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…at room temperature and under atmospheric pressure of hydrogen, syn -product 6a was obtained as the major diastereomer with >99% conversion and 88:12 dr within 2 h (entry 1). This result demonstrated that, compared to the previous strategy for Pd/C catalyzed hydrogenation of 1 , furnishing the primary amide to N -tosyl amide did induce remote chirality control of the hydrogenation, which improved the diastereoselectivity considerably. The reaction of compound 5a under the same conditions (entry 2) showed that the exocyclic carboxylic acid moiety could also induce remote chirality control to generate 7a as the major diastereomer, albeit with a lower dr (83:17).…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…at room temperature and under atmospheric pressure of hydrogen, syn -product 6a was obtained as the major diastereomer with >99% conversion and 88:12 dr within 2 h (entry 1). This result demonstrated that, compared to the previous strategy for Pd/C catalyzed hydrogenation of 1 , furnishing the primary amide to N -tosyl amide did induce remote chirality control of the hydrogenation, which improved the diastereoselectivity considerably. The reaction of compound 5a under the same conditions (entry 2) showed that the exocyclic carboxylic acid moiety could also induce remote chirality control to generate 7a as the major diastereomer, albeit with a lower dr (83:17).…”
mentioning
confidence: 73%
“…Various synthetic strategies for brivaracetam have been reported in due course (Scheme a) . In the initial studies, the target enantiomer of brivaracetam was usually obtained via the separation of racemic mixtures by chiral HPLC …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The methyl‐substituted pyrrolidinone 3 z was obtained in good yield and enantioselectivity. Variation of the alkyl chain was well accepted, which permitted the synthesis of 3 aa and 3 ab , structural derivatives of brivaracetam [18] and pregabalin , [19] thus highlighting the potential of the protocol to access biologically relevant scaffolds. A thioether moiety was well tolerated ( 3 ac ), while alicyclic‐substituted esters resulted in enhanced enantioselectivity (products 3 ad and 3 ae ).…”
Section: Figurementioning
confidence: 99%
“…Amides bearing a stereogenic center in the α-position are frequently observed architectures in pharmaceuticals, natural products, and their intermediates. 1 For example, aliskiren 2 and captopril 3 are commonly prescribed pharmaceuticals for the treatment of hypertension, whereas brivaracetam 4 and levetiracetam 5 exhibit anticonvulsant properties for the treatment of epilepsy (Figure 1 ). The synthesis of such chiral motifs is therefore of high interest in organic synthesis.…”
Section: Table 1 Optimization Of the Reaction Condition...mentioning
confidence: 99%